Effect of desipramine and fluoxetine on energy metabolism of cerebral mitochondria. (25th August 2016) - Villa, Roberto Federico; Ferrari, Federica; Gorini, Antonella; Brunello, Nicoletta; Tascedda, Fabio
Graphical abstract: Highlights: Desipramine and fluoxetine effects on rat frontal cortex energetics were assessed. Mitochondrial energy metabolism was studied by Functional Proteomics. Somatic mitochondria and synaptic ones were purified. Energy metabolism increased in somatic mitochondria, decreased in synaptic. The drugs modified enzyme activities coherently with their pharmacodynamics. Abstract: Brain bioenergetic abnormalities in mood disorders were detected by neuroimaging in vivo studies in humans. Because of the increasing importance of mitochondrial pathogenetic hypothesis of Depression, in this study the effects of sub-chronic treatment (21 days) with desipramine (15 mg/kg) and fluoxetine (10 mg/kg) were evaluated on brain energy metabolism. On mitochondria in vivo located in neuronal soma (somatic) and on mitochondria of synapses (synaptic), the catalytic activities of regulatory enzymes of mitochondrial energy-yielding metabolic pathways were assayed. Antidepressants in vivo treatment modified the activities of selected enzymes of different mitochondria, leading to metabolic modifications in the energy metabolism of brain cortex: (a) the enhancement of cytochrome oxidase activity on somatic mitochondria; (b) the decrease of malate, succinate dehydrogenase and glutamate-pyruvate transaminase activities of synaptic mitochondria; (c) the selective effect of fluoxetine on enzymes related to glutamate metabolism. These results overcome the conflicting data so far obtained with antidepressants on brain energy metabolism, because the enzymatic analyses were made on mitochondria with diversified neuronal in vivo localization, i.e. on somatic and synaptic. This research is the first investigation on the pharmacodynamics of antidepressants studied at subcellular level, in the perspective of (i) assessing the role of energy metabolism of cerebral mitochondria in animal models of mood disorders, and (ii) highlighting new therapeutical strategies for antidepressants targeting brain bioenergetics.